Healthy behaviours and productive activities among Thai older adults: A repeated cross-sectional analysis. (September 2018) - Witvorapong, Nopphol
Abstract: Based on a nationally representative repeated cross-sectional sample of older individuals from the 2007 and 2011 Surveys of Older Persons in Thailand (n = 50, 138, with the participation rate of 95.79%), this study investigates the extent to which healthy behaviours are interrelated with productive activities in old age. Healthy behaviours were represented by alcohol abstinence, tobacco abstinence, physical exercise, and consumption of a nutritious diet, encompassing all major lifestyle choices that could lower mortality risks among the general population. Productive activities were represented by social participation and labour participation, consistent with the paradigms of Active and Productive Ageing promoted by the World Health Organization. A multivariate probit model, whereby all six behaviours were jointly estimated, was explored. Conditional on pairwise combinations of the two productive activities, the probabilities of contemporaneously undertaking all four healthy behaviours were calculated. The results illustrate that the relationships among productive activities and health behaviours are inextricable and complex. Considering each of the four healthy behaviours separately, social participation and labour participation are associated with lower probabilities of abstaining from alcohol and tobacco but higher probabilities of exercising and keeping a nutritious diet among older adults. Considering all four healthy behaviours together, the productive activities are associated with a significant increase in the probability that a Thai older adult would simultaneously abstain from alcohol, abstain from tobacco, exercise, and eat healthily, compared to if the same individual undertakes neither social participation nor labour participation. This study calls for a consistent set of multiple-behaviour interventions to promote healthy and productive ageing. Highlights: Productive activities in old age include social and labour participation. They motivate positive & negative behavioural changes among older Thais. They are associated with lower probabilities of alcohol and tobacco abstinence. They are associated with higher probabilities of exercising & healthy dieting. Coherent multiple-behaviour interventions are needed to promote healthy ageing.